Effect of vitrification at different meiotic stages on epigenetic characteristics of bovine oocytes and subsequently developing embryos. (26th July 2021) - Yodrug, Thatawat; Parnpai, Rangsun; Hirao, Yuji; Somfai, Tamas
Abstract: Vitrification by the Cryotop method is frequently used for bovine oocyte cryopreservation. Nevertheless, vitrified oocytes still have reduced developmental competency compared with fresh counterparts. The objective of this study was to compare the effect of vitrification either at the germinal vesicle (GV) stage or at the metaphase II (MII) stage on epigenetic characteristics of bovine oocytes and subsequently developing embryos. Our results demonstrated that vitrification of oocytes at each meiotic stage significantly reduced blastocyst development after in vitro fertilization (IVF). However, vitrification at the GV stage resulted in higher blastocyst development than did vitrification at the MII stage. Irrespective of the meiotic stage, oocyte vitrification did not affect 5‐methylcytosine (5mC) immunostaining intensity in oocyte DNA. However, at both stages, it caused a similar reduction of 5mC levels in DNA of subsequently developing blastocysts. Oocyte vitrification had no effect on the intensity of H3K9me3 and acH3K9 immunostaining in oocytes and subsequent blastocysts. The results suggest that irrespective of meiotic stage, oocyte vitrification alters global methylation in resultant embryos although such alteration in the oocytes was not detected. Oocyte vitrification might not influence histone acetylation and methylation in oocytes and resultant embryos. Vitrification at the immature stage was more advantageous for blastocyst development than at the mature stage.